Macrobrachium agwi - a new species of freshwater prawn (Decapoda: Palaemonidae) from East Bengal, India - Klotz, Werner (Zootaxa, 2008)
Freshwater prawns do not only have economic importance in hydroponics and fisheries for food purposes, but also recently receive increasing attention in aquarium trade (Karge & Klotz 2007). An examination of some prawns imported as ‘ornamental shrimps’ from Cooch Behar, East Bengal, India to Europe revealed that they belong to a hitherto undescribed species of the genus Macrobrachium and are described here in detail. The new species belong to the group of specimen with large eggs, indicating abbreviated or direct larval development in freshwater, occurring in inland river systems (Tiwari 1955b). Morphological M. agwi nov.sp. is most similar to M. kempi (Tiwari, 1947) first described from Chittagong, Bangladesh, M. altifrons altifrons (Henderson, 1893) from Northern India and Nepal and M. hendersoni (De Man, 1906) known from hill streams in East India and Myanmar. Though the proposed new species can be distinguished from M. kempi by lacking a dense fur of setae on the lower margin of the propodus of male large cheliped, from M. altifrons by the shape and armature of second chelae and from M. hendersoni by lacking longitudinal groves covered with fine hairs on fingers of second chelipeds.